Supplier Selection Model of the Lithium-ion Battery using Fuzzy AHP and Analysis of BOCR - Wardayanti, Ari; Zakaria, Roni; Sutopo, Wahyudi; Louhenapessy, Bendjamin (Unijourn Publisher, 2018)
Although the demand for the lithium-ion battery for electronic consumers and electric vehicles in Indonesia is high, there is no supplier coming from the local manufacturer. The proper selection of suppliers is required by some lithium-ion battery manufacturers (cells, modules, and packs), and Research and Development (R&D) center of the lithium-ion battery with the consideration not only in benefits and cost but also in opportunities and risks. It is important that experts assist the manufacturers and R&D to procure the lithium-ion (materials and cells), through transparent methods that seek a quantitative model to select the right supplier. The main objective of this study is to propose an analytical approach to select suppliers which incorporate Benefits, Opportunities, Costs and Risks (BOCR) concept that comply with the characteristics of the lithium-ion battery industries. A fuzzy Analytical Hierarchy Process (AHP) model is developed by accommodating the vagueness and inaccuracies of expert elections. The result of this research is development of the model obtained from 2 questionnaires given to the expert. Questionnaire 1 was made for the determination of criteria and sub-criteria, while Questionnaire 2 aims to perform pairwise comparisons of existing criteria and sub-criteria. In the selection of the lithium-ion battery suppliers, there are 11 criteria and 40 sub-criteria which are considered. Those criteria are divided into 4 merits and known for their respective global priorities.